Effects of volatile anaesthetics on heme metabolism in a murine genetic model of Acute Intermittent Porphyria: A comparative study with other porphyrinogenic drugs - Ruspini, Silvina Fernanda (2018)
Background: Acute Intermittent Porphyria (AIP) is an inherited disease produced by a deficiency of Porphobilinogen deaminase (PBG-D). The aim of this work was to evaluate the effects of Isoflurane and Sevoflurane on heme metabolism in a mouse genetic model of AIP to further support our previous proposal for avoiding their use in porphyric patients. A comparative study was performed administering the porphyrinogenic drugs allylisopropylacetamide (AIA), barbital and ethanol, and also between sex and mutation using AIP (PBG-D activity 70% reduced) and T1 (PBG-D activity 50% diminished) mice. Methods: The activities of 5-Aminolevulinic synthetase (ALA-S), PBG-D, Heme oxygenase (HO) and CYP2E1; the expression of ALA-S and the levels of 5-aminolevulinic acid (ALA) were measured in different tissues of mice treated with the drugs mentioned. Results: Isoflurane increased liver, kidney and brain ALA-S activity of AIP females but only affected kidney AIP males. Sevoflurane induced ALA-S activity in kidney and brain of female AIP group. PBG-D activity was further reduced by Isoflurane in liver male T1; in AIP male mice activity remained in its low basal levels. Ethanol and barbital also caused biochemical alterations. Only AIA triggered neurological signs similar to those observed during human acute attacks in male AIP being the symptoms less pronounced in females although ALA-S induction was greater. Heme degradation was affected. Discussion: Biochemical alterations caused by the porphyrinogenic drugs assayed were different in male and female mice and also between T1 and AIP being more affected the females of AIP group. General significance: This is the first study using volatile anaesthetics in an AIP genetic model confirming Isoflurane and Sevoflurane porphyrinogenicity.